2017
DOI: 10.4172/2167-0269.1000283
|View full text |Cite
|
Sign up to set email alerts
|

Guests’ Motives to Write Positive and Negative Hotel Reviews on Trip Advisor

Abstract: This study aims to examine which motives and review components drive hotel guests to write positive and negative reviews on Trip advisor. It tests the motives of writing an online review after the guest has written an online review. Respondents are only Trip advisor users who had left an online review message on Egyptian 5-star hotel services in the last year. Primary data was collected using a Web-based survey. Using regression analysis, the results concluded that there are differences between guests' motives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The results show that even hotels that use traditional management systems are forced to incorporate the ratings out of fear of losing their market share. The study shows that OHRs are not only a major source of information for consumers (Ghazi, 2017), who are willing to pay higher prices for services with a good score (Mellinas et al, 2016). This information has internal effects on hotel managers.…”
Section: Influence Of Online Hotel Reviewsmentioning
confidence: 92%
See 3 more Smart Citations
“…The results show that even hotels that use traditional management systems are forced to incorporate the ratings out of fear of losing their market share. The study shows that OHRs are not only a major source of information for consumers (Ghazi, 2017), who are willing to pay higher prices for services with a good score (Mellinas et al, 2016). This information has internal effects on hotel managers.…”
Section: Influence Of Online Hotel Reviewsmentioning
confidence: 92%
“…In regard to hotels, statistics show that online reviews have become the major source of information for consumers (Ghazi, 2017). One of the greatest strengths of researching customer ratings is that ratings can show overall customer satisfaction in a direct way (Zhao et al, 2019) by representing information based on the actual experiences of customers (Gretzel and Yoo, 2008).…”
Section: The Effect Of Online Hotel Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media and review sites create challenges but also offer connections opportunity between tourists and make it easier to interact with satisfied or dissatisfied customers. These sites also create satisfaction and other topics research opportunities, as demonstrated in studies based on review platforms, web questionnaires, and social media analyses (Filieri, Alguezaui, & McLeay, 2015;Ghazi, 2017).…”
Section: Introductionmentioning
confidence: 99%